The Quranic Hermeneutics: Unity in Text, Diversity in Interpretation - Bhat, Ali Muhammad (Journal of Quranic Sciences and Research, 2025)
The Quran, revealed in Arabic, stands as the foundational religious scripture and the principal source of guidance for all of humanity, particularly for Muslims across the globe. Its language embodies both classical eloquence and colloquial resonance. As the primary medium of religious and intellectual discourse, Arabic exerted a far-reaching influence, prompting individuals worldwide to engage with divine revelation. Many were driven to understand the Quran’s deeper meanings and the context of its revelation through learning its original language. However, for the vast majority across different regions and linguistic backgrounds, mastering Arabic was not feasible. This gave rise to a pressing need to translate the Quran into various native languages, aiming to make its message comprehensible to broader audiences. In numerous instances, translations and interpretations were manipulated to align with specific agendas, leading to distortions, misinterpretations, and widespread skepticism. Therefore, a critical exploration of Quranic translation is essential, not only to understand its historical and linguistic challenges but also to identify effective strategies for preserving the integrity of the message.